Role of the chaperonin TCP-1 ring complex in protein aggregation and neurodegeneration - Vanlalrinchhani Varte; Diego E. Rincon-Limas; Diego E. Rincon-Limas; Diego E. Rincon-Limas (Frontiers in Molecular Neuroscience, 2025)
The chaperonin TCP-1 ring complex (TRiC), also known as chaperonin-containing TCP-1 (CCT) complex, plays a crucial role in protein folding and quality control within the cell. Comprising eight distinct subunits (CCT1 - CCT8), TRiC assists in the folding of a wide range of client proteins, ensuring their proper conformation and functionality. This mini review explores the assembly, structure, and cellular functions of TRiC and discusses its involvement in protein aggregation and neurodegenerative diseases. We emphasize the emerging role of CCT2 in modulating the formation of abnormal amyloid aggregates, including amyloid beta, tau, and polyglutamine (polyQ) deposits, which are central to the pathogenesis of various neurological conditions. Lastly, we provide evidence supporting the neuroprotective role of CCT2 in vivo and also highlight therapeutic implications and key unresolved questions in the field, offering a foundation for new research opportunities.